Comparison of Two Combinations of Maximum Medical Therapy for Lowering Intraocular Pressure in Primary Open-angle Glaucoma - Wy, Seoyoung; Kim, Young Kook; Jeoung, Jin Wook; Park, Ki Ho; Ha, Ahnul (Korean journal of ophthalmology, 2020)
We sought to compare the efficacy as well as the safety of two maximum medical therapy combinations applied to lower the intraocular pressure (IOP) in different primary open-angle glaucoma (POAG) age groups. This was a retrospective, consecutive case series study that included 60 eyes of 60 subjects with POAG, specifically 20 subjects aged 40 to 54 years, 21 aged 55 to 69 years, and 19 aged 70 years or older. All had been treated for at least 12 months with triple maximum medical therapy (TMT; dorzolamide/timolol, brimonidine, and latanoprost) to lower their IOP, which subsequently was changed to double maximum medical therapy (DMT, fixed drug combinations of tafluprost/timolol and brinzolamide/brimonidine). The rate of IOP change and adverse drug reactions were compared amongst the three age groups. The mean IOP change at three months after converting from TMT to DMT was -0.65 ± 1.42 mmHg (-3.84% ± 9.31%) among the overall study group, but this finding was not statistically significant ( = 0.108). In the 40 to 54 years and 55 to 69 years groups, the mean IOP change rates were +0.29 ± 0.96 mmHg (+2.40% ± 6.85%, = 0.087) and -0.50 ± 0.99 mmHg (-3.05% ± 6.40%, = 0.084) respectively. In the 70 years or older group, the mean IOP change, interestingly, was -1.80 ± 1.46 mmHg (-11.29% ± 9.31%, < 0.001) and nine (47.4%) of the 19 subjects showed additional IOP reductions of 10% or more after converting from TMT to DMT. In all three age groups, the incidence rate of dry eye was significantly lower for DMT than for TMT ( = 0.031). In POAG patients, DMT was proven to be both effective and safe for lowering the IOP, especially in those 70 years or older group, when compared with the TMT protocol.